Use of 3p technology to rationalize production: field research costs in the General Company for Automotive & Equipment Industry / Alexandria (Journal of Accounting and Financial Studies ( JAFS ), 2018)
Nowadays competitive business environments, the introduction of new products from the global market and evaluation of the optimal procurement of goods from a global point of view .necessary The completion of companies develop and strengthen their position in the market by manufacturing the highest quality of finished products more efficiently, at the lowest cost, and bring them to the market. And the development of the new product and needs to start a new process serving production through the application of production preparation process (3p). Production process 3p is a lean approach. This work focuses on minimizing product waste, designing process and using it to eliminate damage in existing processes. However, the first axis dealt with the research methodology, including the problem, the objective and the hypothesis of research. The second axis dealt with concepts and technical steps 3p. The third axis dealt with the practical aspect in the General Company for Industry, The reason for this research was to demonstrate lean. concepts, which can be effective, and plan them effectively and efficiently.